Observations of a middle atmosphere thermal structure over Durban using a ground-based Rayleigh LIDAR and satellite data - (:unkn) unknown (My University, 2012)
Studying the middle atmospheric thermal structure over southern Africa is an important activity to improve the understanding of atmospheric dynamics of this region. Observations of a middle atmosphere thermal structure over Durban, South Africa (29.9°S, 31.0°E) using the Durban Rayleigh Light Detection and Ranging (LIDAR) data collected over 277 nights from April 1999 to July 2004, including closest overpasses of the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) and Halogen Occultation Experiments (HALOE) satellites, are presented in this paper. There seems to be good agreement between the LIDAR and satellite observations. During autumn and winter, the temperatures measured by the LIDAR in the height region between 40 km and 55 km were 5 K to 12 K higher than those measured by the satellites. The data from the LIDAR instrument and the SABER and HALOE satellites exhibited the presence of an annual oscillation in the stratosphere, whereas in the mesosphere, semi-annual oscillations dominated the annual oscillation at some levels. The stratopause was observed in the height range of ~40 km - 55 km by all the instruments, with the stratopause temperatures measured as 260 K - 270 K by the LIDAR, 250 K - 260 K by the SABER and 250 K - 270 K by the HALOE. Data from the SABER and HALOE satellites indicated almost the same thermal structure for the middle atmosphere over Durban.
Keywords: African Research